2015
DOI: 10.1128/aem.00903-15
|View full text |Cite
|
Sign up to set email alerts
|

Living in an Extremely Polluted Environment: Clues from the Genome of Melanin-Producing Aeromonas salmonicida subsp. pectinolytica 34mel T

Abstract: d Aeromonas salmonicida subsp. pectinolytica 34mel T can be considered an extremophile due to the characteristics of the heavily polluted river from which it was isolated. While four subspecies of A. salmonicida are known fish pathogens, 34melT belongs to the only subspecies isolated solely from the environment. Genome analysis revealed a high metabolic versatility, the capability to cope with diverse stress agents, and the lack of several virulence factors found in pathogenic Aeromonas. The most relevant phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 96 publications
(97 reference statements)
0
15
0
Order By: Relevance
“…The masoucida subspecies, which is evolutionarily close to M18076‐11, does not exhibit the presence of the A‐layer when tested on CBB agar. It is well known that some subspecies of A. salmonicida , such as pectinolytica and most salmonicida , produce a brown diffusible pigment (Griffin et al., ; Pavan et al., ). Upon investigation, it was discovered that strain M18076‐11 also produced a brown diffusible pigment, but the colour was not as intense as in other salmonicida subspecies, and it presented a more orange hue than a brown one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The masoucida subspecies, which is evolutionarily close to M18076‐11, does not exhibit the presence of the A‐layer when tested on CBB agar. It is well known that some subspecies of A. salmonicida , such as pectinolytica and most salmonicida , produce a brown diffusible pigment (Griffin et al., ; Pavan et al., ). Upon investigation, it was discovered that strain M18076‐11 also produced a brown diffusible pigment, but the colour was not as intense as in other salmonicida subspecies, and it presented a more orange hue than a brown one.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, this characteristic has been used as a taxonomic marker to differentiate between Aeromonas species (Martin‐Carnahan & W. Joseph, ), but recent results challenge this assumption. The subspecies pectinolytica of the salmonicida species has the capacity to grow at 37°C (Pavan, Abbott, Zorzópulos, & Janda, ), as opposed to the other four officially recognized subspecies ( salmonicida, smithia, achromogenes and masoucida ), which are psychrophilic (Martin‐Carnahan & W. Joseph, ; Pavan, Pavan, López, Levin, & Pettinari, ). Furthermore, other putative A. salmonicida subspecies were recently reported to have the ability to grow at 37°C, confirming that pectinolytica is not an exception, while hinting at a greater phenotypic diversity in A. salmonicida than previously estimated and shedding light on an intraspecies lifestyle dichotomy (Vincent et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been generally reported that the inactivation of HmgA, an enzyme that degrades HGA into maleylacetoacetate, results in pyomelanin production in many species, including mesophilic A. salmonicida subsp. pectinolytica (50)(51)(52)(53). By examining the hmgA genes of A. salmonicida subsp.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli, a representative fecal bacterium belonging to Enterobacteriaceae, can widely adapt to a variety of mammalian bodies, including animal or human intestines. These bacteria contain plasmids that encode drug resistant genes, resulting in the constant release of bacteria to natural environments such as rivers or soil, as has been documented in many studies of bacteria such as Salmonella or E. coli . Moreover, Aeromonas spp., including A. caviae, are representative natural environmental bacteria that are widely distributed in coastal areas and rivers as a fish pathogen, as well as in many areas in which people live and thus serve as a potential reservoir for the plasmid.…”
Section: Discussionmentioning
confidence: 99%